Financial markets and R&D investments - Marco Mazzoli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper introduces a discrete-time intertemporal investment model in which the flow of profits affects the risk premium on the cost of finance, and, as a consequence, the rate of discount of future profits. While public investments, according to a consolidated literature, constitute the main bulk of innovation policies, this model is used to comment and interpret the potential use of another, secondary, public policy, consisting of tax incentives for firms performing R&D expenditures and issuing securities in the stock market. Linking public policies for innovation to the stock market might help to reduce the problems of discretionality and the monitoring of public expenditure used to finance R&D and technical innovation.
Keywords: D92; G32; 330; investment; intertemporal firm choice; capital structure; financing policy; Betriebliche Forschung; Betriebliche Investitionspolitik